A new inequality-sensitive multidimensional deprivation index (MDI) for dichotomous variables - José Espinoza-Delgado; Jacques Silber (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
In this paper, we propose to use the so-called Sen-Shorrocks poverty index (Shorrocks, 1995) to measure multidimensional deprivation when only dichotomous variables are available to assess deprivation in the various deprivation domains, the most common case in the literature, and introduce a rank-dependent multidimensional poverty index for multiple binary indicators using a counting approach. The resulting multidimensional deprivation index, or MDI for short, also has a nice graphical representation that is derived from the TIP curve of Jenkins and Lambert (1997). The great advantage of measuring multidimensional deprivation using the MDI is that this index is sensitive to inequality and can be fully broken down by deprivation domain, as well as by population subgroups, two features that have far-reaching policy implications and have proven to be important for poverty analysis. An empirical illustration based on deprivation data from four Central American countries (Guatemala, El Salvador, Honduras, and Nicaragua) shows the usefulness of the MDI, as it allows us to conclude, for example, that in each country, education contributes the most (about 30%) to multidimensional poverty.
Keywords: I3; I31; I32; D6; D63; O1; 330; Multidimensional poverty analysis; Inequality; Gini index; Dominance